Analysis of the Financial Performance of Companies Experiencing Audit Delay and Market Reaction - Nurwidayani, Nurwidayani; Fahrunnisa, Fahrunnisa; Rahman, Bagus Arif; Sulistyowati, Wiwit Apit (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study aims to analyze financial performance trends in companies experiencing audit delays, in terms of ROA, ROE and DER, and to examine the impact of these trends on market reactions, such as share prices and TVA. Design/methodology/approach: This study uses a quantitative approach, with a population of 53 companies. The sample was determined using purposive sampling techniques, with 20 companies meeting the criteria. The study period was two years (2021-2022), so the sample data analyzed amounted to 40. Secondary data obtained from IDX was used and descriptive analysis methods were employed. Findings: The results of this study indicate that companies experiencing audit delays show a downward trend in ROA, ROE and TVA values. DER values show an upward trend, while share prices remain stable. Research limitations/implications: The limitations focus on companies listed on the IDX, and the data used in this study is limited to the period 2021-2022. Practical implications: The practical implications of this study for investors regarding delays in the submission of audited financial reports can be used to assess a company's financial performance and make decisions on stock market purchases and capital investment. Originality/value: This paper original. Paper type: Research paper.